Assessing the capacity of Ghana to introduce health technology assessment: a systematic review of economic evaluations conducted in Ghana. (25th October 2020) - Addo, Rebecca; Goodall, Stephen; Hall, Jane; Haas, Marion
Abstract : Objectives: Ghana is in the process of formally introducing health technology assessment (HTA) for health decision making. Similar to other low- and middle-income countries, evidence suggests that the lack of data and human capacity is a major barrier to the conduct and use of HTA. This study assessed the current human and data capacity available in Ghana to undertake HTA. Methods: As economic evaluation (EE) forms an integral part of HTA, a systematic review of EE studies undertaken in Ghana was conducted to identify the quality and number of studies available, methods and source of data used, and local persons involved. The literature search was undertaken in EMBASE (including MEDLINE), PUBMED, and Google Scholar. The quality of studies was evaluated using the Consolidated Health Economics Evaluation Reporting Standards. The number of local Ghanaians who contributed to authorship were used as a proxy for assessing human capacity for HTA. Results: Thirty-one studies were included in the final review. Overall, studies were of good quality. Studies derived their effectiveness, resource utilization and cost data mainly from Ghana. The most common source of cost data was from the National Health Insurance Scheme pricing list for medicines and tariffs. Effectiveness data were mostly derived from either single study or intervention programs. Sixty out of 199 authors were Ghanaians (30 percent); these authors were mostly involved in data collection and study conceptualization. Conclusions: Human capacity for HTA in Ghana is limited. To introduce HTA successfully in Ghana, policy makers would need to develop more local capacity to undertake Ghanaian-specific HTA.